Occlusion of primary dentition in preschool children of Chennai and Hyderabad: A comparative study - C H Sriram; V Krishna Priya; N Sivakumar; K R Maheshwar Reddy; P Jitendra Babu; Pujita Reddy (Wolters Kluwer Medknow Publications, 2012)
Objective : To provide information on the state of occlusion and the spaces available after complete eruption of the primary dentition and to compare the characteristic features of the primary dentition in Chennai and Hyderabad, two of the metropolitan cities in South India. Materials and Methods : Children in the age range between 3 and 5 years were selected from different schools of both Chennai and Hyderabad, with a complete set of primary dentition. Study casts were obtained and assessment of spacing in the primary dentition and the primary molar relationship were recorded in centric occlusion. The data obtained was subjected to statistical analysis. Results : The mean values and standard deviations for the primary molar relationship and spacing in primary dentition are given in the tables. Conclusion : Bilateral flush terminal plane relationship of the second primary molars and spaced dentition was most frequent in primary dentition of the children in both Chennai and Hyderabad groups. Significant differences were not found among both groups and genders.